ORIENTASI BEKERJA MENURUT PERSPEKTIF ISLAM - Edy Junaedi; Anton Hindardjo (Jurnal Asy-Syukriyyah, 2016)
Want to work for a company where employees are satisfied with the culture and values? Glassdoor has announced its report of the Top 25 Companies for Culture & Values, based on workplace insights shared by the people who know companies best — the employees. The companies stand out for high culture & values ratings and insightful reviews. Facebook truly values the important things in life. The culture and dialog is open about, The people are friendly and helpful. The culture fosters hard work and fun (Southwest Airlines). Everyone shares a common goal to make the best products for the consumer, and it shows in most (Apple), Amazing company to work for. Good culture, fun, high energy and lots of reasons to stay (Nike), The culture in the plant is very positive and I feel like everyone wants to help one another (Procter & Gambler) and people of Google said The culture is amazing too. Each employee does not mind helping the other out if they are stuck. There are some of corporations that make praud for their employees. Amazing culture come from value that happened by employee and management of corporation every day and every day, the culture is positif and everyone can do the right thing and want to help another, these are value of Islam-Ukhuwah and Falah, So we can do anything full motivated and dedicated togather we can. Values of corporation are being easy to say and remember, easy to do because come from soul of corporation’s people and universal value of corporation make Performance better